As questões de gênero no trabalho de coordenação pedagógica - SILVA, Marcileide Vieira da (2019)
The present Work of Conclusion of Course entitled "The gender relations in the work of pedagogical coordination" has as a line of research gender and education and, by general objective to analyze how the gender issues emerge in the exercise of the pedagogical coordination function. Specifically, it sought to identify how the work of pedagogical coordination is developed by male and female professionals in their teaching levels and also to map the similarities and differences in the work of male coordinators and female pedagogical coordinators by considering their characteristics, similarities and differences. It is understood that pedagogical coordination needs to have environments and professionals that enable the practice of values, equality and respect between people of different sexes and allow education to live with all the possibilities related to the subjectivities of men and women. The research is characterized in a qualitative approach, aided by a bibliographical research based on Deslauriers (2001), Gil (1991) and Richardson (2010), respectively. The theoretical framework was based on the contributions of scholars such as Saviani (2003), Libâneo (2017), Vianna (2001), Louro (1997), Scott (1995), Apple (1988), among others, in the areas of gender and pedagogical coordination. As a technique for data collection, we used interviews and questionnaires, based on Trivinos (1990) and, for data analysis; we opted for content analysis based on Chizzotti (2010). The research subjects were four pedagogical coordinators, two men and two women from municipal and state schools located in the municipality of Abaetetuba-PA. As a result, it was identified that the professionals interviewed recognize that this function of pedagogical coordination is carried out with dedication, commitment, and responsibility for both genders. Being a differential, pointed out by the interviewees, the organization by the women and the firmness towards the men, besides that the coordinators are multipliers of knowledge, in which the articulation between theory and practice becomes the central axis of training of educators as reflective professionals. It was also concluded that the reflection on gender in school spaces, because there is a relationship with the entire school community in the process of building and conducting educational policies. Lastly, the daily routine of pedagogical coordinators and coordinators is limited to carrying out their assignments, which are concomitant with unplanned activities, and often outside their respective tasks and responsibilities, since in each space the possibilities of coordination and, so the limits of the scope of your work also expand.